Process evaluation of an implementation trial to improve the triage, treatment and transfer of stroke patients in emergency departments (T(3) trial): a qualitative study - McInnes, Elizabeth (Implement Sci, 2020)
BACKGROUND: The implementation of evidence-based protocols for stroke management in the emergency department (ED) for the appropriate triage, administration of tissue plasminogen activator to eligible patients, management of fever, hyperglycaemia and swallowing, and prompt transfer to a stroke unit were evaluated in an Australian cluster-randomised trial (T(3) trial) conducted at 26 emergency departments. There was no reduction in 90-day death or dependency nor improved processes of ED care. We conducted an a priori planned process influential factors that impacted upon protocol uptake. METHODS: Qualitative face-to-face interviews were conducted with purposively selected ED and stroke clinicians from two high- and two low-performing intervention sites about their views on factors that influenced protocol uptake. All Trial State Co-ordinators (n = 3) who supported the implementation at the 13 intervention sites were also interviewed. Data were analysed thematically using normalisation process theory as a sensitising framework to understand key findings, and compared and contrasted between interviewee groups. RESULTS: Twenty-five ED and stroke clinicians, and three Trial State Co-ordinators were interviewed. Three major themes represented key influences on evidence uptake: (i) Readiness to change: reflected strategies to mobilise and engage clinical teams to foster cognitive participation and collective action; (ii) Fidelity to the protocols: reflected that beliefs about the evidence underpinning the protocols impeded the development of a shared understanding about the applicability of the protocols in the ED context (coherence); and (iii) Boundaries of care: reflected that appraisal (reflexive monitoring) by ED and stroke teams about their respective boundaries of clinical practice impeded uptake of the protocols. CONCLUSIONS: Despite initial high ‘buy-in’ from clinicians, a theoretically informed and comprehensive implementation strategy was unable to overcome system and clinician level barriers. Initiatives to drive change and integrate protocols rested largely with senior nurses who had to overcome contextual factors that fell outside their control, including low medical engagement, beliefs about the supporting evidence and perceptions of professional boundaries. To maximise uptake of evidence and adherence to intervention fidelity in complex clinical settings such as ED cost-effective strategies are needed to overcome these barriers. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry (ACTRN12614000939695).